Do spatial and recognition memories have a lateralized processing by the dorsal hippocampus CA3? - Pimentel, Gabrielle Araujo [UNESP]; Crestani, Ariela Maltarolo [UNESP]; Florindo, Luiz Henrique [UNESP] (Elsevier, 2022)
The present study evaluated the function of the right and left CA3 of the dorsal hippocampus (dHPC) in the processing of (i) recognition memory, (ii) recent and remote spatial memory, (iii) working memory and (iv) navigation strategy. Wistar rats were divided into four experimental groups: vehicle group (VG), animals received a bilateral injection of phosphate-saline buffer (PBS) in both right and left dorsal CA3; dHPC-R group, animals received an injection of ibotenic acid (IBO) in the right dorsal CA3; dHPC-L group, animals received an IBO injection in left dorsal CA3; and dHPC-Bi group, animals received bilateral injections of IBO in both dorsal CA3. Rats were submitted to a sequence of behavioral tests: Morris water maze (MWM), object recognition test (ORT), forced T-maze and MWM 30 days after the first exposure. The results showed no evidence of functional lateralization and the dorsal CA3 does not seem to be essential for learning and memory (recent and remote) processing and allocentric navigation analyzed in the MWM and T-maze, respectively. However, rats with right or bilateral lesions in the dorsal CA3 failed to recognize the familiar object in the ORT, suggesting a lateralized processing of recognition memory. That result is unprecedented and contributes to the knowledge about the compartmentalization of HPC functions.
Keywords: Dorsal CA3; Dorsal hippocampus; Episodic memory; Functional lateralization; Recognition